Improving Students’ Achievement in Reading Comprehension Through Learning Together Method - Sundari Ulfa (REGISTER: Journal of English Language Teaching of FBS-Unimed, 2012)
ABSTRACT This study focuses on improving students’ achievement in reading comprehension by applying the Learning Together Method. This research was conducted with an action research design. The subject of this study was the first year  IPA students at SMA Nur Azizi Tanjung Morawa. The total  number of students was 32 students. This research was performed in two cycles and every cycle consisted of three meetings. The quatitative data was collected through a reading test and the qualitative data through diary notes, observation sheets, and interview. The reading test showed that the score of the students improved continuously from pre test through post test 1 and post test 2. The mean of the students’ score in pre test was 60,5. In post test 1, the mean increased to 69,4 and in post test 2, the score rose to 83. The diary notes, observation sheets, and interview indicated that the students were eager and more active during teaching and learning process in the second cycle than in the first cycle. It was found that teaching reading through the Learning Together Method improved students’ achievement. It is suggested that English teachers apply this method as one alternative in teaching reading comprehension.   Key Words: Learning Together Method, Reading Comprehension, Students’ Achievement.